Aspiration as a Function of Age, Sex, Liquid Type, Bolus Volume, and Bolus Delivery Across the Healthy Adult Life Span. (January 2018) - Butler, Susan G.; Stuart, Andrew; Markley, Lisa; Feng, Xin; Kritchevsky, Stephen B.
Objectives: The purpose of this investigation was to examine, via flexible endoscopic evaluation of swallowing (FEES), factors that affect penetration and aspiration during swallowing across the adult lifespan. Methods: Healthy adults (N = 203) across the third to ninth decades of life participated. Penetration Aspiration Scale (PAS) scores were assessed during FEES as a function of age, sex, liquid type (water and skim, 2%, and whole milk), volume (5, 10, 15, and 20 ml), and delivery (cup and straw). Results: The PAS scores differed significantly by liquid type ( P < .0001) and age group ( P < .0001). In general, PAS scores were higher for milk versus water swallows and for older age groups. Significant interactions of liquid type by age ( P = .0042) and sex by volume ( P = .020) were also evidenced. In addition, the odds of penetration and aspiration increased significantly with milks compared to water and age ( P < .05). Increased bolus volume also increased the odds of aspiration ( P < .05). Conclusions: Aspiration may be an underappreciated phenomenon in healthy adults. The inclusion of both water and milk test boluses of various volumes during FEES may be important for the appropriate assessment of adult penetration and aspiration.